ENHANCING TOURISM EXPERIENCES THROUGH EFFICIENT LOGISTICS AND SUPPLY CHAIN PRACTICES - Mishra, Krishna Kumar; Singh, Chandan; Mishra, Shekhar Kumar; Soni, Kartik (ShodhKosh: Journal of Visual and Performing Arts, 2024)
In the contemporary tourism industry, efficient logistics and supply chain practices play a crucial role in enhancing visitor experiences and ensuring sustainable growth. This paper explores the impact of optimized logistical operations and robust supply chain management on the tourism sector, highlighting how these practices contribute to improved service quality, reduced operational costs, and increased customer satisfaction. Through a comprehensive review of existing literature and case studies from diverse geographical regions, this research identifies key strategies and innovations that have successfully integrated logistics and supply chain efficiencies into tourism operations. The findings demonstrate that strategic coordination between transportation providers, accommodation services, and local suppliers not only enhances the overall tourist experience but also fosters economic benefits for local communities. By presenting a model framework for the implementation of effective logistics and supply chain solutions in tourism, this study provides valuable insights for policymakers, industry stakeholders, and researchers aiming to optimize the tourism value chain. The paper concludes with recommendations for future research directions and practical implications for achieving a competitive advantage in the global tourism market through logistics and supply chain excellence.